Systemic therapy in cervical cancer: 30 years in review. (May 2019) - Liontos, Michalis; Kyriazoglou, Anastasios; Dimitriadis, Ioannis; Dimopoulos, Meletios-Athanasios; Bamias, Aristotelis
Graphical abstract: Abstract: Advanced-inoperable cervical cancer is a challenging entity due to increased percentage of locoregional and distant recurrences. Furthermore, recurrent cervical cancer not amenable to radical treatment as well as de novo metastatic disease are considered incurable with dismal prognosis. Well-designed clinical trials conducted during the last 30 years have revealed the active chemotherapeutic agents as well as their optimal combinations. The rational approach that has led to the current treatment algorithms as well as the introduction of targeted therapies based on the knowledge of the molecular pathogenesis of the disease are discussed in this review.